Lithographic processing of polymers using plasma-generated electron beams - Caolo, Mary Ann, author; Hiraoka, Hiroyuki, author; Collins, George J., author; Yu, Zengqi, author; Krishnaswamy, Jayaram, author; Li, Lumin, author; IEEE, publisher (Colorado State University. Libraries, 1990)
Pattern definition in polymer films is achieved using electron beams generated in soft vacuum (0.05-0.50 torr) glow discharges either on a continuous or pulsed (20-100 ns) basis. With the continuous- mode electron beam, 7- µm transmission mask features are replicated in both polymethyl methacrylate (PMMA) and polyimide resists. Using a pulsed electron-beam submicron (~0.5 µm) features are transferred from an electron-transmitting stencil mask into the PMMA. The soft-vacuum pulsed electron beam is also eminently suited for polymer stabilization. Pulsed electron-beam hardening of 0.05-3.5- µm-thick AZ-type and MacDermid resist patterns is also demonstrated with hardened resist patterns stable to temperatures between 200° and 350°C. The demonstrated replication and pattern stabilization technique may be applicable in microelectronics packaging lithography where the resist thickness is substantial, linewidths are 1-10 µm, and registration requirements are less stringent.
Keywords: electron beam lithography; plasma applications; polymer films